Pengaruh Model Pembelajaran Cooperative Integrated Reading and Composition Terhadap Reading Comprehension Achievement Siswa Disekolah Berbasis Pondok. - Safitri, Alfi Fatimatus; Rusijono, Rusijono; Mariono, Andi (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The purpose of this study was to determine the effect of the CIRC learning model on students' reading comprehension achievement in boarding schools. The method used is experimental by comparing the results of the pre-test and post-test of the control class with the results of the pre-test and post-test of the experimental class. The subjects of this study were 70 boarding students who were divided into a control class and an experimental class. This study uses the independent samples t test analysis technique with the results showing that sig. (2-tailed) is 0.000 <0.05, which means that there is a significant difference between the final score of the control class and the experimental class. The cooperative integrated reading and composition (CIRC) learning model has an effect on increasing students' active roles in the learning process and improving students' reading comprehension achievement